Evolution of diverse host infection mechanisms delineates an adaptive radiation of lampsiline freshwater mussels centered on their larval ecology - Hewitt, Trevor L.; Haponski, Amanda E.; Foighil, Diarmaid Ó. (PeerJ, 2021)
North American watersheds contain a high diversity of freshwater mussels (Unionoida). During the long-lived, benthic phase of their life cycle, up to 40 species can co-occur in a single riffle and there is typically little evidence for major differences in their feeding ecology or microhabitat partitioning. In contrast, their brief parasitic larval phase involves the infection of a wide diversity of fish hosts and female mussels have evolved a spectrum of adaptations for infecting host fish with their offspring. Many species use a passive broadcast strategy: placing high numbers of larvae in the water column and relying on chance encounters with potential hosts. Many other species, including most members of the Lampsilini, have a proactive strategy that entails the use of prey-mimetic lures to change the behavior of the hosts, i.e., eliciting a feeding response through which they become infected. Two main lure types are collectively produced: mantle tissue lures (on the female’s body) and brood lures, containing infective larvae, that are released into the external environment. In this study, we used a phylogenomic approach (ddRAD-seq) to place the diversity of infection strategies used by 54 North American lampsiline mussels into an evolutionary context. Ancestral state reconstruction recovered evidence for the early evolution of mantle lures in this clade, with brood lures and broadcast infection strategies both being independently derived twice. The most common infection strategy, occurring in our largest ingroup clade, is a mixed one in which mimetic mantle lures are apparently the predominant infection mechanism, but gravid females also release simple, non-mimetic brood lures at the end of the season. This mixed infection strategy clade shows some evidence of an increase in diversification rate and most members use centrarchids (Micropterus & Lepomis spp.) as their predominant fish hosts. Broad linkage between infection strategies and predominant fish host genera is also seen in other lampsiline clades: worm-like mantle lures of Toxolasma spp. with sunfish (Lepomis spp.); insect larvae-like brood lures (Ptychobranchus spp.), or mantle lures (Medionidus spp., Obovaria spp.), or mantle lures combined with host capture (Epioblasma spp.) with a spectrum of darter (Etheostoma & Percina spp.) and sculpin (Cottus spp.) hosts, and tethered brood lures (Hamiota spp.) with bass (Micropterus spp.). Our phylogenetic results confirm that discrete lampsiline mussel clades exhibit considerable specialization in the primary fish host clades their larvae parasitize, and in the host infection strategies they employ to do so. They are also consistent with the hypothesis that larval resource partitioning of fish hosts is an important factor in maintaining species diversity in mussel assemblages. We conclude that, taking their larval ecology and host-infection mechanisms into account, lampsiline mussels may be legitimately viewed as an adaptive radiation.
Keywords: Phylogenomics; Unionidae; RADseq; Parasitism